2006
DOI: 10.1115/1.2397140
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Raney-Nickel Catalysts for Alkaline Fuel Cell Applications

Abstract: Platinum and other platinum group metals, either as singles or in combinations, have been preferred for use in low temperature fuel cells, mainly alkaline fuel cells (AFCs), polymer membrane electrolyte fuel cells (PEMs), and direct methanol fuel cells (DMFCs), for hydrogen oxidation reaction (HOR). However, also the Raney-nickel catalyst, which is among the most active non-noble metals for the HOR, has been the target of interest, especially in AFCs. However, electrodes with nonsupport Raney-nickel catalysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…One can distinguish several groups of catalytic materials having metallic nickel as the main component. Among them, there are metal-doped-sponge Raney nickel catalysts, electrochemically deposited bulk double- and ternary-metal catalysts, highly dispersed supported Ni-based catalysts, and single-crystal Ni facets . The first group, Raney nickel catalysts, is the most popular, with the highest number of studies, because of its popularity in liquid electrolyte (KOH)-based alkaline fuel cells.…”
Section: Hor Electrocatalystsmentioning
confidence: 99%
“…One can distinguish several groups of catalytic materials having metallic nickel as the main component. Among them, there are metal-doped-sponge Raney nickel catalysts, electrochemically deposited bulk double- and ternary-metal catalysts, highly dispersed supported Ni-based catalysts, and single-crystal Ni facets . The first group, Raney nickel catalysts, is the most popular, with the highest number of studies, because of its popularity in liquid electrolyte (KOH)-based alkaline fuel cells.…”
Section: Hor Electrocatalystsmentioning
confidence: 99%
“…in the region of approximately 80%) and have a thermodynamic fuel cell voltage of 1.23V at 25°C [40]. Although low temperature (25 to 75°C) AFC's have preferentially used platinum and platinum group metals either separately or in combination, the use of Raney-nickel catalyst has been subject to increasing interest due to it being one of the most active nonnoble metal catalysts for the hydrogen oxidation reaction [41,42].…”
Section: Alkaline Fuel Cell Electrodementioning
confidence: 99%
“…The Kiros group [103] showed that doping Raney nickel with Cr, La, Ti, Cu, and Fe could have positive effects on the activity and stability of the catalysts. Linnekoski et al [97] reported that mechanically alloying Raney nickel and carbon using a ball mill with the addition of 2 wt% Pt remarkably improved the performance of the fuel cell.…”
Section: Raney Nickelmentioning
confidence: 98%
“…Although Raney nickel has excellent hydrogen adsorption ability and relatively large surface area, some disadvantages have also been reported, such as high electrolyte diffusion resistance due to low pore volume and small pore size [98,99], and insufficient conductivity [97]. One type of mitigation is to support Raney nickel on carbon blacks, which will decrease its electrolyte diffusion resistance and increase its electrical conductivity [97].…”
Section: Raney Nickelmentioning
confidence: 98%
See 1 more Smart Citation